Faith, “Fetish,” and the Making of Kongo Christianity: Missionary Collecting and the Shifting Meanings of Kongo Crucifixes in Late Colonial Northern Angola - Amaral, Ana Rita (Material religion, 2025)
This article explores the interplay between missionary collecting and the socio-historical dynamics that shaped the acquisition of a series of crucifixes and other items from Kongo clan chiefs in northern Angola in the 1950s. Focused on the collections of Dutch Spiritan Jan Vissers, it examines the conflicting and shifting value of crucifixes, and how Christianity and heritage were negotiated and transformed.